Dexamethasone Is Superior to Dexmedetomidine as a Perineural Adjunct for Supraclavicular Brachial Plexus Block: Systematic Review and Indirect Meta-analysis. (March 2019) - Albrecht, Eric; Vorobeichik, Leon; Jacot-Guillarmod, Alain; Fournier, Nicolas; Abdallah, Faraj W.
Abstract : BACKGROUND: Both dexamethasone and dexmedetomidine are effective peripheral nerve block (PNB) perineural adjuncts that prolong block duration. However, each is associated with side effects. With paucity of head-to-head comparisons of these adjuncts, the question of the best adjunct to mix with local anesthetics (LA) for PNB is unanswered. This meta-analysis aims to inform current practice and future research by identifying the superior adjunct by comparing dexamethasone and dexmedetomidine. METHODS: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, trials comparing the combination of perineural dexamethasone or dexmedetomidine with LA to LA alone for PNB were sought. The Cochrane Risk of Bias Tool was used to assess the methodological quality of trials, and indirect or network meta-analyses using random-effects modeling were planned. We designated duration of analgesia as a primary outcome. Secondary outcomes included sensory and motor block durations, sensory and motor block onset times, and the risks of hypotension, sedation, and neurological symptoms. RESULTS: Fifty trials were identified, including only 1 direct comparison, precluding a network meta-analysis. Indirect meta-analysis of 49 trials (3019 patients) was performed. Compared to dexmedetomidine, dexamethasone prolonged the duration of analgesia by a mean difference (95% confidence interval [CI]) of 148 minutes (37–259 minutes) ( P = .003), without prolonging sensory/motor blockade. Dexmedetomidine increased rates of hypotension (risk ratio [95% CI], 6.3 [1.5–27.5]; P = .01) and sedation (risk ratio [95% CI], 15.8 [3.9–64.6]; P = .0001). Overall risk of bias was moderate, and publication bias was noted, resulting in downgrading evidence strength. CONCLUSIONS: There is low-quality evidence that both adjuncts similarly prolong sensory/motor blockade. However, dexamethasone may be a superior adjunct; it improves the duration of analgesia by a statistically significant increase, albeit clinically modest, equivalent to 2.5 hours more than dexmedetomidine, without the risks of hypotension or sedation. Future direct comparisons are encouraged.